Using Orthodontic Wire electrodes in Gel Electrophoresis Device - Basma Faihan; Eman Ghadhban Khalil; Ziad T. Al-Dahan; Ilham A. Jasim (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Gel electrophoresis is an essential device in biology laboratories and life science centers for the analysis of macromolecules such as DNA, RNA, and protein. This separation technique mainly depends on using a set of electrode wires to generate an electric field within the gel medium. The most common failure is the electrode wire cut. This fault is due to corrosion or inadvertent cut of the thin platinum wire. Platinum wires are delicate, expensive, and not available in local markets. In this paper, orthodontic nickel-free stainless steel wire (diameter = 0.5 mm), is used as an alternative to the Platinum wire. The effectiveness of the orthodontic stainless steel wire was confirmed under high-level voltages (100, 150, and 250 Volts), and the data produced was reasonable, with good visualization of DNA fragments. However, the Anode wire experienced corrosion after about 11 hours, while the cathode is still effective. The study concluded that while not a long-term solution, nickel-free stainless steel orthodontic wire offers a simple, inexpensive (< $1) alternative to platinum electrodes for gel electrophoresis, especially for students and researchers conducting short-term experiments. However, using stainless steel with nickel is suggested to potentially enhance the lifespan of the electrodes due to nickel's contribution to corrosion resistance. Further research is recommended to explore its wider applications in molecular biology research and improve experimental procedures using this alternative electrode materiale.